A Literature Study On The Implementation Of Merdeka Curriculum - Muhammad Rafi Zidan; Zaitun Qamariah (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
The Indonesian education system has been changed over past few decades. There are several reason of these changes but the one most crucial aspect of these changes is the student and technology. Merdeka curriculum or also known as independent study is this modern era’s newest curriculum, as we know in this current world technology has been developed in the speed of light and it also affects students’ character toward studying and that’s why the Merdeka curriculum being made. The main purpose of this curriculum is to use tech as useful as possible and also to develop each unique ability that students. This article’s main purpose is to explain about format and implementation of the Merdeka curriculum in this modern era.